In planta distribution, accumulation, movement and persistence of Citrus tristeza virus in citrus host - and K. K. BISWAS*, A. TARAFDAR, P.D. GHOSH1 (Indian Phytopathology, 2012)
In planta accumulation of Citrus tristeza virus (CTV) in different plant tissues of infected citrus host was determined using enzyme linked immuno-sorbent assay (ELISA) and reverse transcriptase polymerase chain reaction (RT-PCR). CTV was not found to be evenly distributed in all the plant parts. The tender bark of 6 months to 1 year old, petiole and mid rib of young leaves, and apical bud showed high amount of CTV. The result was confirmed by RT-PCR assay showing amplicons of coat protein (CP) gene (672 nt) of CTV genome. Infected acid (Kagzi) lime (C. aurantifolia) and sweet orange (Mosambi) (C. sinensis) trees harbored accumulated higher amount of virus than Darjeeling mandarin (C. reticulata). However, the severity of symptom caused by CTV in acid lime could not be correlated to virus titer. CTV was found to move faster in acid lime and sweet orange than mandarin tree. It was observed that virus persisted up to 180 days in crude sap prepared with 0.05 M phosphate buffer, pH 7.0 stored at 4Â°C, but only up to 2-4 days in same crude sap kept at 25-32Â°C.